Seismic Retrofitting of Steel Frames with Buckling Restrained and Ordinary Concentrically Bracing Systems with Various Strain Hardening and Slenderness Ratios - Gholamreza Abdollahzadeh; Heidar Farzi-Bashir; Mohammadreza Banihashemi (Journal of Rehabilitation in Civil Engineering, 2014)
The present study assesses the seismic performance of steel moment resisting frames (SMFs) retrofitted with different bracing systems. Two structural configurations were utilized: ordinary concentrically braces (OCBFs), buckling-restrained braces (BRBFs). A 7-story and 18-story steel perimeter SMFs were designed with insufficient lateral stiffness to satisfy code drift limitations in high seismic hazard zone. The frames were then retrofitted with OCBFs with 30, 60, 90, 120 slenderness ratios and BRBFs. Inelastic time-history analyses have been carried out using OPENSEES software for strain hardening from 1 to 10 percent to assess the structural performance under earthquake ground motions. Inter story drifts were employed to compare the inelastic response of the retrofitted frames. It is shown that the distribution of maximum story drifts in the height of BRBFs is more uniform than OCBFs with various slenderness ratios and with increasing strain hardening, the inter story drift and P-∆ effects is decreased. In addition, normal buckling braces with low slenderness ratio behave similar to the BRBFs to control inter story drift, but the cycling behavior in dissipation the energy can’t be changed, and finally the suitable performance from BRBF can’t be obtained.